IFRS Adoption and the Quality of Loss Recognition in Emerging Markets: A Case Study on the Casablanca Stock Exchange. - EL IDRISSI RIOUI Samia; TOUICHER Ouardia (African Scientific Journal, 2024)
Abstract The International Financial Reporting Standards (IFRS), issued by the International Accounting Standards Board (IASB), are increasingly becoming the preferred accounting framework among companies in African countries. Research on the impact of IFRS adoption on the quality of financial reporting in emerging economies remains scarce. Therefore, this paper examines the effect of IFRS adoption on timely loss recognition, a key indicator of financial reporting quality. The financial data from 34 companies listed on the Casablanca Stock Exchange, covering the period from 2009 to 2019, are analyzed using logistic regression within a quantitative econometric methodology. Two balanced panels were created: one consisting of 14 companies that adopted IFRS, and the other comprising 20 companies following Moroccan accounting standards. The results indicate that the quality of earnings (as measured by timely loss recognition) did not improve after IFRS adoption. This finding suggests that accounting regulators and bodies in African countries should encourage a more rigorous application of IFRS by continuously training accountants and auditors of listed companies on the practical implementation of these standards. Such training should be mandatory and easily accessible. Keywords: IFRS Standards; Timely Loss Recognition; Logistic Regression; Listed Companies.